Indonesia Rancang Bangun Alat Ukur Konsentrasi Rhodamin B Menggunakan Sensor TCS34725 Berbasis Arduino UNO pada Kerupuk Bewarna - Zakhiah, Putri; Firmawati, Nini (Universitas Andalas, 2025)
Food safety is a critical aspect, particularly regarding the use of hazardous dyes such as Rhodamine B, which can cause liver damage and increase cancer risk if consumed excessively. This study developed a system to detect and measure the concentration of Rhodamine B in red crackers using the TCS34725 sensor. The system utilizes the sensor to measure the colour intensity of samples, which is processed using an Arduino UNO and displayed as RGB values that are converted into Rhodamine B concentrations. The detection results are displayed on an LCD (Liquid Crystal Display) screen and complemented with a buzzer as an alarm. Validation was conducted by comparing the system's measurements with a UV-Vis spectrometer across a wavelength range of 400 nm to 600 nm for 10 Rhodamine B concentration variations, ranging from 0.5 ppm to 5 ppm. Testing was also performed on 10 red cracker samples through an extraction process. The results showed that the system achieved an accuracy of 93.86%, with a maximum wavelength of 553 nm. Two samples were detected to contain Rhodamine B at concentrations of 4.98 ppm and 5.11 ppm, respectively. This system is effective as a practical and accurate tool for ensuring food safety.